Effect of nutritional intervention on weight multidisciplinary ambulatory patients - María Luisa Fallas (Universidad de Costa Rica, 2012)
This retrospective descriptive study is based on statistical data generated in the outpatient nutritional support of Dr. RA Calderon Guardia Hospital. Educate the patient and their family. Further, the nutritional plans and nutritional supplementation given by the multidisciplinary group shows a weight gain of 74% of the study group. The sample population was 156 patients who presented during calendar 2011. The population consisted of 100 patients who had at least 2 evaluations in 2011. The analysis evaluated the impact of nutritional interventions on body weight of those treated. At each patient examination, weight was measured in kilograms (kg), height in meters, body mass index as (kg/m2), and changes in weight in kilograms. The spreadsheet designed and used for data and graphs was Word 2003 and Excel 2003. The doctor and a nurse specialist trained in nutritional support, the team was complete the sample. Variables were: Age, Sex, Patient Diagnosis Regarding the outcome of patients treated in the outpatient, nutritional support found that 74 patients gained weight which represents 74% of the sample group, 4 patients (4%) were able to maintain weight, and 22 patients (22%) continued to lose weight. A multidisciplinary approach to nutritional support allows most of patients by their pathology or malnutrition to submit increased risk of suffering, can improve or maintain their nutritional status